Karakteristik Fisikokimia dan Organoleptik Sirup Campuran Buah Pandan Tikar (Pandanus tectorius Park.) dan Nenas (Ananas comosus) - Wiwiyen Manurung; Zita Letviany Sarungallo; Eduard Fransisco Tethool; Cicilia Maria Erna Susanti; Nurhaidah Iriany Sinaga; Diana Nurini Irbayanti; Rossa Marlen Martha Latumahina (Jurnal Aplikasi Teknologi Pangan, 2021)
Pandan tikar (Pandanus tectorius Park.) fruit has a strong flavor and nutritious, but it has not been utilized as a food ingredient. This study aims to determine the physicochemical and organoleptic characteristics of pandan tikar syrup, which is compared with pineapple syrup. The study was conducted by experiment with five treatments of combination concentration of pandan tikar and pineapple that are P1 (100%:0%), P2 (50%:50%), P3 (75%:25%), P4 (90%:10%), and P5 (0%:100%). The results of this study indicate that the characteristics of pandan tikar syrup (P1) has a natural color of brownish yellow, sweet taste, pandan aroma, with acidity (pH) 4, total dissolved solids 55-60 oBrix, viscosity 1.5-2.0 cP and vitamin C 60-75 mg/100g. The addition of pineapple fruit decreases the color intensity of pandan tikar fruit syrup and Vitamin C content, but it does not affect the acidity, total dissolved solids and viscosity. The results of organoleptic tests on color, aroma, taste and overall appearance indicate that the panelists prefer pandanus syrup (P1) rather than pineapple syrup (P5).